Banishment by a Thousand Laws: Residency Restrictions on Sex Offenders - Corey Rayburn Yung (Washington University Law Review, 2007)
In this Article, I argue that the establishment of exclusion zones by states and localities is a form of banishment that I have termed “internal exile.” Internal exile is an uncommon practice in modern developed societies. Consequently, the increasing emergence of exclusion zones is a development that could fundamentally alter basic principles of the American criminal justice system. This Article is structured as follows: Part I explores the history and law of banishment as a form of punishment in the West generally and then specifically in the United States. Part II discusses the development of sex offender exclusion zone laws and judicial responses to those laws. Part III identifies the connections between the historical practices of banishment discussed in Part I and the new exclusion zone laws reviewed in Part II. Part IV shows how these connections ultimately raise substantial legal, policy, and ethical problems for residency restrictions on sex offenders. I conclude by looking to the future of sex offender laws in America.
Keywords: Exile (Punishment); Sex offender registration; Exclusionary zoning